The Interpretation of Leontief's System–A Reply - Klein, L. R. (Review of Economic Studies, 1956)
Journal Article The Interpretation of Leontief's System—A Reply Get access L. R. Klein L. R. Klein Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 69–70, https://doi.org/10.2307/2296239 Published: 01 July 1956